دور التحليل المالي في تقييم أداء المصارف الاسلامية الجزائرية - بن عامر, زبير (جامعة الوادي University of Eloued, 2020)
من خلال هذا المقال نحاول ابراز دور التحليل المالي في تقييم الأداء المالي للمصارف الاسلامية الجزائرية، حيث تم التطبيق على إحدى تلك المصارف، والمتمثل في مصرف السلام الجزائرومن خلال القيام بدراسة مقارنة مع كلا من مصرف الثقة كعينة عن المصارف الخاصة، والبنك الخارجي الجزائري كعينة عن المصارف العمومية، وذلك خلال الفترة الممتدة من سنة 2013 إلى غاية سنة 2017. من خلال الدراسة التحليلة توصلنا إلى أن مصرف السلام يحتل أفضل مرتبة بالنسبة لكل من مؤشرات السيولة ومؤشرات الربحية، فيما سجل مصرف الثقة أفصل ملاءة مالية وأكثر توظيفا لأمواله. وتوصي الدراسة مصرف السلام بضرورة توظيف فوائضه من السيولة قصد تحقيق ربحية أعلى في المستقبل. Through this article, we try to highlight the role of financial analysis in evaluating the financial performance of Algerian Islamic banks, as it was applied to one of these banks, represented by the Al-Salam Bank Algeria, and through a comparative study with both the Trust Bank as a sample for private banks, and the Algerian Foreign Bank as a sample for Public banks, during the period from 2013 to 2017. Through the analytical study, we came to the conclusion that Al-Salam Bank ranks the best in terms of both liquidity and profitability indicators, while Trust Bank recorded the best financial solvency and the most use of its money. The study recommends that Al-Salam Bank should use its surplus liquidity in order to achieve higher profitability in the future.
The role of financial analysis in evaluating the performance of Algerian Islamic banks - A comparative study of Al Salam Bank with the Trust Bank and the Algerian Foreign Bank for the period: (2013-2017) -
مقال
Keywords: التحليل المالي ; مؤشرات السيولة ; مؤشرات الربحية ; الملاءة المالية ; مؤشرات التوظيف